1975
DOI: 10.1093/infdis/132.2.189
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the Transport and Toxicity of Cephalosporins in the Kidney

Abstract: Large doses of cephaloridine cause acute necrosis of the proximal renal tubule that can be prevented by probenecid and other organic anions. Although there is little or no net secretion of cephaloridine by the mammalian kidney, the degree of cephaloridine uptake by the cortex of the rabbit kidney is substantial; this uptake is also prevented by probenecid and other organic anions. Cortical concentrations of cephaloridine were measured in control and probenecid-treated animals of different mammalian species. Ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
32
0
16

Year Published

1979
1979
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(51 citation statements)
references
References 16 publications
3
32
0
16
Order By: Relevance
“…In the present study, CER at a dose of 600 mg/kg induced glucosuria, proteinuria and reduction of the glomerular filtration rate (GFR). The reduction in the tubular reabsorption rate of water seems to be due to the reduction of GFR (7,8).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the present study, CER at a dose of 600 mg/kg induced glucosuria, proteinuria and reduction of the glomerular filtration rate (GFR). The reduction in the tubular reabsorption rate of water seems to be due to the reduction of GFR (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…The decrement by KW-3902 of CER-induced toxicity might be ascribed to a dilution of CER in the proximal tubule due to the diuretic effect of KW-3902, which acts mainly on proximal tubules (18). The decreased concentration of CER in the proximal tubule could result in the attenuated nephrotoxicity of CER, which mainly injures the prox imal tubule (8).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…12,13 Some cephalosporins, such as cephaloridine, have severe nephrotoxicity, and it is suggested that their toxic effect is related to the transport systems in the renal proximal tubules. 14 Transport of β-lactam antibiotics mediated by renal organic anion transporter has an important influence on their pharmacokinetics and toxicokinetics. Among human organic anion transporters, OAT1 (SLC22A6) and OAT3 (SLC22A8) are PAH/dicarboxylate exchangers, and are localized on the basolateral side of the proximal tubules, whereas OAT4 (SLC22A11) is localized on the apical side of the proximal tubules.…”
Section: ) Elimination From the Kidneymentioning
confidence: 99%